Evaluasi Penggunaan Sistem Informasi Manajemen Rumah Sakit Dengan Metode TAM Di RSUD Ir. Soekarno Kabupaten Sukoharjo - Herlinda Kartika Maharani; I Putu Juni Andika; Tunjung Sri Yuliati; Yovita Prabawati Tirta Dharma (Journal of Health, Medical, and Psychological Studies, 2026)
This study aims to evaluate the use of Hospital Management Information Systems (SIMRS) at RSUD Ir. Soekarno Sukoharjo using the Technology Acceptance Model framework. A quantitative descriptive approach with a cross-sectional design was employed, involving 54 respondents selected through total sampling. Data were collected using structured questionnaires based on key TAM constructs, including perceived ease of use, perceived usefulness, attitude toward using, behavioral intention to use, and actual usage. The findings indicate that users generally perceive SIMRS as easy to use and beneficial in supporting healthcare service processes. These perceptions significantly contribute to the formation of positive user attitudes and strengthen behavioral intentions to continuously use the system. Furthermore, actual usage is reflected in consistent and routine system utilization in daily operational activities. However, some limitations remain, particularly related to the optimization of advanced features and system efficiency. The study highlights that successful implementation of SIMRS depends not only on user acceptance but also on continuous system improvement and user capacity development. Strengthening training programs and enhancing technical performance are essential to maximize system effectiveness and improve the overall quality of healthcare services.